2022
DOI: 10.1186/s12894-022-01078-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment and relevant clinical impact of randomized controlled trials on chronic prostatitis/chronic pelvic pain syndrome

Abstract: Objective This study evaluated the quality of randomized controlled trials (RCTs) on chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS). Methods We searched PubMed, Web of Science, and Embase for RCTs (original articles) on CP/CPPS published from database establishment to 2021. The RCT quality assessment was performed using the Consolidated Standards of Reporting of Trials (CONSORT) statement and the improved Jadad scale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It is now recommended by the British Urology Association that the main aim of CP/CPPS treatment is to mitigate functional damage to patients [ 42 ], usually with single internal and external fascia manipulation. However, most of the studies on myofascial release therapy are pre-and post-controlled trials while lacking high-quality randomized controlled trials [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is now recommended by the British Urology Association that the main aim of CP/CPPS treatment is to mitigate functional damage to patients [ 42 ], usually with single internal and external fascia manipulation. However, most of the studies on myofascial release therapy are pre-and post-controlled trials while lacking high-quality randomized controlled trials [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a therapeutic regimen for CP is lacking, and there are currently no effective drugs for CP (Franco et al, 2019; S. J. Liu, Gao, et al, 2022; Magistro et al, 2016). Therefore, the discovery of novel, safe, and effective drugs is a top priority for the prevention and treatment of CP (Franco et al, 2018; Pena et al, 2021; Zhao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Primary studies, especially randomized controlled trials (RCT), often provide the most direct and powerful evidence in medical practice, making them the "gold standard" for assessing the effectiveness and safety of medical interventions [11]. A recent study suggested that the quality of RCT reports of CP/CPPS needs to be further improved and that the results of RCT of CP/CPPS should be treated with caution [12]. Additionally, the SRs/MAs are considered vital evidence for the development of clinical practice guidelines and can inform healthcare policy as well as clinical decision-making [13,14].…”
Section: Introductionmentioning
confidence: 99%